2022
DOI: 10.1186/s13012-022-01247-y
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for de-implementation of low-value care—a scoping review

Abstract: Background The use of low-value care (LVC) is a persistent problem that calls for knowledge about strategies for de-implementation. However, studies are dispersed across many clinical fields, and there is no overview of strategies that can be used to support the de-implementation of LVC. The extent to which strategies used for implementation are also used in de-implementing LVC is unknown. The aim of this scoping review is to (1) identify strategies for the de-implementation of LVC described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 106 publications
1
16
0
1
Order By: Relevance
“…Possible reasons for that could be that the information received from the participants about possible contingencies were not sufficiently comprehensive. Those identified in this study were only a few out of several suggested in the literature (7,10,49). Alternative contingencies with a stronger influence on behaviors related to using x-rays could potentially have maintained unnecessary use of LVC despite the two strategies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Possible reasons for that could be that the information received from the participants about possible contingencies were not sufficiently comprehensive. Those identified in this study were only a few out of several suggested in the literature (7,10,49). Alternative contingencies with a stronger influence on behaviors related to using x-rays could potentially have maintained unnecessary use of LVC despite the two strategies.…”
Section: Discussionmentioning
confidence: 80%
“…The current state-of-the-art is that strategies should match the local factors impacting behavior rather than expecting particular implementation strategies to always be superior to others (9). With regard to de-implementation, numerous local factors have been found to influence the use of LVC, including care processes, financial incentives, and perceived pressure from patients, other professionals, or the system (7,(10)(11)(12). However, there is insufficient knowledge about which factors might be relevant for choosing effective strategies.…”
Section: Introductionmentioning
confidence: 99%
“…evidence of benefit and ease of use) 23 . A recent scoping review of strategies for de-implementation of low-value care found that with a few exceptions similar strategies are used for de-implementation and implementation 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance in deimplementation is deciding what practices to deimplement, which must involve considerations of equity, clinical effectiveness, cost‐effectiveness, and patient preferences. More studies are needed to understand methods for identifying deimplementation targets and to identify the most effective deimplementation strategies 12 …”
Section: Areas Of Interest For Implementation Sciencementioning
confidence: 99%
“…More studies are needed to understand methods for identifying deimplementation targets and to identify the most effective deimplementation strategies. 12…”
Section: And Concern For Omission (Or Missing a Diagnosis) Over Commi...mentioning
confidence: 99%